How social media marketing influences consumers purchase decision? A mediation analysis of brand awareness - Fajar Ardiansyah; Endi Sarwoko (University of Islam Malang, 2020)
The important usage of social media as highly interactive platforms of communications is bound to change the way companies approach marketing. Many previous studies conclude that social media has proven to be a key factor in creating brand awareness. Thus, a higher level of awareness will affect consumers' decisions positively. However, few studies focus on the role of brand awareness as a mediation construct in affecting purchase decisions. Therefore, this study aims to explore the mediation role of brand awareness on the relationship between social media marketing and purchase decisions. The study conducted is quantitative research based on a survey approach. Purposive sampling and ordinary least square regression were used as sampling techniques and data analysis. The study revealed that social media marketing has a positive and significant influence on both brand awareness and purchase decisions. Unfortunately, this study failed to prove the direct and indirect effect of brand awareness on purchase decisions. The nature of wetsuit (sportswear) that can be categorized as a high involvement product was considered as the main reason for the insignificancy effect of brand awareness on purchase decision and the mediation role of brand awareness. In the case of high involvement products, consumers tend to be rational so that they were required more time and effort to evaluate specific product performances and characteristics.